Empirical macromodels under test: a comparative simulation study of the employment effects of a revenue neutral cut in social security contributions - Herbert S. Buscher; Hermann Buslei; Klaus Göggelmann; Henrike Koschel; Fred Ramb; Tobias F. N. Schmidt; Viktor Steiner; Peter Winker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
In the paper we simulate a revenue-neutral cut in the social security contribution rate using five different types of macro- / microeconomic models, namely two models based on time-series data where the labour market is modelled basically demand oriented, two models of the class of computable equilibrium models which are supply oriented and finally a firm specific model for international tax burden comparisons. Our primary interest is in the employment effects the models predict due to the cut in the contribution rate. It turns out that qualitatively all models considered predict an increase in employment three years after the cut. But the employment effects differ considerably in magnitude, which follows immediately from the different behavioral assumptions underlying the different models. – – In dem Beitrag wird der Beschäftigungseffekt infolge einer aufkommensneutralen Senkung der Sozialversicherungsbeiträge simuliert. Zu diesem Zweck werden fünf unterschiedliche ökonomische Modelle verwendet, namentlich zwei Modelle, die auf Zeitreihendaten aufbauen und in denen der Arbeitsmarkt überwiegend von der Nachfrageseite dominiert wird, zwei Modelle aus der Klasse der computable equilibrium models, die typischerweise angebotsorientiert sind, und ein mikroökonomisches, firmenspezifisches Steuerbelastungsvergleichsmodell. Alle Simulationsergebnisse der Modelle weisen auf einen, wenngleich teilweise kleinen, positiven Beschäftigungseffekt hin, der sich allerdings beträchtlich in seiner Größenordnung unterscheidet. Dies ist eine unmittelbare Folge aus den unterschiedlichen Verhaltensannahmen, die den einzelnen Modellen unterliegen.
Keywords: C50; E17; H55; C53; 330; Sozialversicherungsbeitrag; Steuerpolitik; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Ökonometrisches Makromodell; Deutschland